(untitled) (Advancements in Homeopathic Research, 2024)
Introduction: Hair loss, or alopecia, is a prevalent concern with medical and cosmetic implications. Hair loss, attributed to genetic predisposition, hormonal imbalances, and psychosocial impacts, necessitates effective treatments. This study aims to assess the safety and efficacy of specific formulations Zauber™ Hair Drops (Zauber™) and Zauberöl® Premium Hair Oil (Zauberöl®) in addressing testosterone induced alopecia, utilizing a rat model. This research contributes to our understanding of potential solutions to the rising prevalence of this condition.Materials and Methods: 60 Male Wistar rats were divided into ten groups. To induce alopecia, testosterone was administered intramuscularly, excluding the normal control group. Experimental groups received distinct treatments, including oral homeopathic drops Zauber™ in mild, moderate and high doses, topical treatment Zauberöl® alone and along with ZauberTM in 3 different doses, and a standard drug, over 28 days. Comprehensive observations and assessments were conducted. Results and Discussion: The results of the study showed that all groups maintained their body weights and food consumption, but those taking Zauber™ and Zauberöl® saw considerable hair follicle growth without severe blood clotting or systemic toxicity, as seen by stable organ weights. The treatment groups showed steady haematological parameters, and sophisticated imaging showed that Zauber™ + Zauberöl® effectively promotes hair follicle growth and development. Higher anagen-to-telogen ratios in treated groups, particularly in the Zauber™ + Zauberöl® groups, show desirable efficiency in alopecia treatment than the standalone therapies. Conclusion: Our study highlights the synergistic therapeutic effects of Zauber™ and Zauberöl® in treating testosterone-induced alopecia in rats, surpassing stand-alone therapies. The observed improvements in various health indicators underscore the potential efficacy and safety of this combined treatment approach.